Concentrated growth factor as an alternative membrane material in periodontal regeneration: a case report - Mohd Noh, Nur Zety; Salehuddin, Nurul Qamar; Ali, Sharul Nisha; Mohamad, Ikhwan Hakimi; Ariffin, Farha (IIUM Press, 2023)
The risk of further periodontal breakdown increases with a deep intrabony defect. Non-surgical periodontal therapy could pose a challenge and surgical intervention is mainly required to manage the defect. Autologous platelet concentrates such as concentrated growth factor (CGF) may improve surgical outcome due to its enrichment with growth factors. Nevertheless, the outcomes of using CGF as a biomaterial in periodontal regenerative therapy is inconclusive. This case report describes the regenerative management of an intrabony defect on all the first molars of a 24-year-old Malay lady diagnosed with Generalised Periodontitis, Stage III, Grade C. A guided tissue regeneration strategy was utilised on all the first molars except on tooth 46, which was treated with xenografts and a biologic adjunct of CGF. Patient was recalled regularly every week up to two months following the procedure, followed by a three-month interval review. The results showed promising outcomes with an average of 4 mm probing pocket depth reduction and 79.1% radiographic bone fill for both regenerative strategies. The utilisation of biologic adjuncts such as CGF, could offer a viable alternative to collagen membrane in periodontal regeneration without compromising clinical results.